Scalar dynamics and implications of ambient air quality management in the EU. Issue 5 (3rd September 2017) - Lenschow, Andrea; Becker, Sara Theresa; Mehl, Catharina
Abstract: This paper presents a comparative case study across 3 countries and 12 cities of the implementation of the EU Ambient Air Quality (AAQ) Directive in order to show that the research perspectives of the scaling literature and the political science discussion on functionally differentiated governance can be usefully combined to reflect on opportunities and constraints in improving environmental governance. Using document and interview material from the cases and employing the policy arrangement approach, we explore how implementing the directive impact on environmental governance in a multi-level system. We demonstrate that the scalar dynamics triggered by the AAQ Directive may create unexpected problems of spatial misfit in term of rules and resources, which ultimately impinge on the effectiveness of the policy in question. Similarly, we find that the territorial rescaling down to the local level is not a panacea for facilitating bottom-up public involvement.